MANAJEMEN RESIKO DAN ANALISIS HAZARD SEBAGAI DASAR MANAJEMEN K3 DI UKM LOGAM (STUDI KASUS: WL ALUMUNIUM) - Tutik Farihah (UIN Sunan Kalijaga Yogyakarta, 2018)
Industrial workplace accidents are accidents that occur in the workplace, especially in industrial environments, where there is no element of intent or sabotage elements in it. Hazard is the activity, objects, components that are considered to cause damage or disruption of the process / activity therein to accidents. WL ALUMUNIUM as SMEs need sustainability production which can not be achieved in case of work accidents or worker safety is not assured due to the existing hazard. Therefore, this research wanted to determine the types of hazards that occur in these SMEs and risk analysis of existing hazard. Hazard Identification (HAZID) is a process of identifying hazards as a first step of determining the risk analysis. There are two main objectives in the hazard identification to obtain a list of hazard and the order based on the level of risk as well as to obtain a qualitative assessment of hazards and ways to reduce the hazard risk level. Based on the processing and analysis that has been done can be seen these SMEs have a hazard which are in the category of Low, Moderate, High and Unacceptable.